“We’re All Victims”: Changes in the Narrative of “National Reconciliation” in Argentina - Salvi, Valentina Isolda (2015)
While the call for ?national reconciliation? as a way to avoid criminal trials for human rights violations has been a constant refrain in the discourse of the armed forces since the return to democracy in Argentina in 1983, it has been made from different positions and in response to diverse conjunctures. Changes in the rhetoric of national reconciliation have been employed as a political and extrajudicial strategy by both the military and civilians for 30 years. The proposal of national reconciliation has oscillated between the need to forget the long-term effects of an "antisubversive war" and a sort of ?duty to remember? in which all Argentines are brothers in the evocation of collective pain.